2022
DOI: 10.1177/15500594221103834
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Electrical Brain Activity and Cognitive Functions Following Mild to Moderate COVID-19: A one-Year Prospective Study After Acute Infection

Abstract: The coronavirus disease 2019 (COVID-19) can disrupt various brain functions. Over a one-year period, we aimed to assess brain activity and cognitive function in 53 COVID-19 patients and 30 individuals without COVID-19 (or asymptomatic). The Montreal Cognitive Assessment, Trail Making Test Parts A and B (TMT-A and B), and Digit Span Test were used to assess cognitive function. Cognitive variables and electroencephalography (EEG) data (activity, mobility, and complexity) were compared between the groups at rest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 66 publications
0
20
2
Order By: Relevance
“…Our results also showed that the effects of COVID-19 infection on cognitive performance and functions were weak; a finding that was in disagreement with the former studies that reported significant adverse effects of both mild and acute COVID-19 on cognition 8,9,11,23 . This finding was somewhat in agreement with Zhou et al 13 who reported no significant difference between their patient group and controls in cognitive functions except for continuous and selective attention, and also another study that found no significant difference between the patient group and controls in terms of cognition 24 .…”
Section: Discussioncontrasting
confidence: 95%
“…Our results also showed that the effects of COVID-19 infection on cognitive performance and functions were weak; a finding that was in disagreement with the former studies that reported significant adverse effects of both mild and acute COVID-19 on cognition 8,9,11,23 . This finding was somewhat in agreement with Zhou et al 13 who reported no significant difference between their patient group and controls in cognitive functions except for continuous and selective attention, and also another study that found no significant difference between the patient group and controls in terms of cognition 24 .…”
Section: Discussioncontrasting
confidence: 95%
“…This assessment is confirmed by different studies which have found EEG abnormalities as possible consequences of neuronal damage provoked by the COVID-19 infection, as evidence of invasion of the CNS and PNS by this virus has become apparent [ 11 ]. These abnormalities have not only been reported on frontal and central changes in the EEG at rest and during high cognitive loads [ 10 , 11 ], but also with brain changes reflecting and atrophy of the crus II for a cognitive decline [ 41 ] and a possible relation with the ACE receptor [ 17 ]. However, some other factors and even treatment procedures (e.g., the prolonged periods of ICU treatment with long-term sedation) are also known as contributors to the impaired functioning of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…These manifestations were mainly reported as cerebrovascular events (strokes), encephalopathies, encephalitis, confusion, and delirium, and in some cases, Guillain-Barré syndrome [ 9 ]. In these cases, the use of electroencephalography (EEG) allows for identifying different abnormalities in the functioning of the CNS, opening the possibility of developing an earlier diagnosis of neurological impairments in critical patients, as well as a prompt proposal of adequate treatments after the infection [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study from Brazil ( Andrei Appelt et al, 2022 ) assessed EEG activity in 53 post-COVID-19 patients and 30 controls at rest and during performance of cognitive tasks including Trail Making Tests (TMT) Parts A and B. In the first group, at 6-12 months after COVID-19, there was a decrease in F3-F7 activity during TMT-B, a reduction in signal complexity at F3-F7 at rest, and a reduction in Fz-F4 activity at rest during TMT-B.…”
Section: Electroencephalography (Eeg)mentioning
confidence: 99%